Susceptibility to Terrorism: Exploring the Case of Ghana in an Insecure Region - Mole, A.M.K. (University of Ghana, 2022)
Although the surge in terrorism has resulted in a corresponding rise in scholarly interests and academic research, the focus has been on terrorism-embattled territories with parameters under investigation straddling the reasons why those countries experience terrorism and violent extremism to the political and socio-economic effects of terrorism. Very scant attention has been paid to countries that have not experienced terrorism and more especially the sources of their immunity to terrorism. As a result, there is a wealth of ignorance and poverty of knowledge on the sources of stability unlike instability from terrorism, which benefits from expost explanations. The purpose of this study therefore, is to seek to identify and empirically examine the sources of Ghana’s resilience to terrorism and violent extremism, relative to her peers in the West African Sub-region. In effect, the question underpinning this study is, why is Ghana less prone to terrorism than her peers in the same region even though they share similar political, socio-economic and demographic characteristics? To yield better insights into the phenomenon under discussion, the study addressed four research questions; (a) is Ghana exposed to the risk of terrorism and violent extremism? (b) why is Ghana less prone to terrorism compared to other countries in the West African sub-region? (c) how is Ghana responding to the threats of Violent Extremism and Terrorism (P/CVET)? (d) how do the chosen responses and mechanism impact Ghana’s P/CVET effort? Methodologically, the study employed a mixed method of data collection and analysis. Data for the study was obtained from multiple sources which included surveys, focus group discussions, expert interviews, and documentary reviews. The study analysis was guided by the research objective/questions and anchored on the Relative Deprivation (RD) theory as the theoretical framework. Based on the analysis of the data gathered and the ensuing discussions, the study concludes that, Ghana’s history and culture of peace; Absence of an overarching religious authority; A thriving democracy and the rule of law; The role and authority of traditional leadership in Ghana; State presence and participatory local governance system and presence of a vibrant media among others are the factors on which Ghana’s resilience to the risk and threats of terrorism is anchored. It also emerged that, Ghana over the years has developed and adopted several domestic and externally sponsored measures respectively, in response to the threat of terrorism and violent extremism. These measures are manifested in legal and policy frameworks, multilateral co-operations, and domestically inspired counter-terrorism strategies. The study makes an inconclusive verdict on the impact of the responses on Ghana’s apparent immunity to terrorism. It nevertheless identifies a number of ways the responses can prop up Ghana's ability to address the underlying drivers of terrorism while remaining relevant in the international war against terrorism. Based on the findings, the study recommended among other things, that in order to prevent the risk factors from exploding into full-blown terrorism, the Government should prioritize addressing the underlying political and socio-economic drivers such as corruption, erosion of trust in institutions, poverty, unemployment and the perception of political marginalisation and exclusion. The study also recommends that the Government work closely with multilateral partners to strengthen the Accra initiative by addressing issues such as financial constraints, language barrier and political will in order to minimise geo-political threats of terrorism.
PhD. Political Science
Keywords: Terrorism; West African Sub-region; Ghana; Relative Deprivation (RD) theory